An overview of phase change materials for construction architecture thermal management in hot and dry climate region. (5th February 2017) - Wahid, Mazlan Abdul; Hosseini, Seyed Ehsan; Hussen, Hasanen M.; Akeiber, Hussein J.; Saud, Safaa N.; Mohammad, Abdulrahman Th.
Highlights: The statistical usage of PCM, and their thermal storage performance in the building are reviewed. PCM materials could be extensively used in building structures to reduce the electricity demand. Paraffin waxes is suitable source for PCM storage in households. Abstract: Worldwide, the demand for environmental friendly energy is ever-increasing due to the rapid growth of economy and living standard. Construction industry being the foremost consumer of material and energy resources has great prospect to developing innovative energy saving and thermally efficient construction materials. Phase change materials (PCMs) as thermal energy storage (TES) systems are potential due to their tailored thermal mass and heat comfort. These latent heat storage (LHS) materials possess extremely high energy storage density than conventional one. Lately, using microencapsulation technology finely dispersed PCMs are incorporated into other materials to create large surface area to improve heat transfer. This article provides a comprehensive overview on the exotic set of features of PCMs, their recent development and future trends with applications directed towards building architectures. Four aspects of PCMs are emphasized: the statistical usage, type, incorporation methods, and their thermal storage performance in the building applications. It is established that PCMs owing to their large heat capacity, high density, and excellent LHS renders as innovative energy saving strategy for sustainable built environment. Furthermore, the inclusion of PCMs in the building parts including walls, floors, and roofs are demonstrated to improve the thermal mass. Consequently, both the energy utilization for space conditioning and extreme temperature variations inside the building gets reduced. The considerable part of electricity is consumed by heating, ventilating, and air conditioning (HVAC) systems during the summer seasons and PCMs technique could be extensively applied in building structures to reduce the electricity demand. Petroleum refining industry produces a wide variety of petroleum products and paraffin wax oil is one of the most important petroleum industry byproducts. Therefore, a valuable source of paraffin waxes is available to be employed as the base PCM storage in households.